Mergers and acquisitions performance within the telecommunications, media and technology sector : case of JSE listed companies - Tshitangano, Tom (University of Cape Town, 2016)
Telecommunications, Media and Technology (TMT) sector also known as the Information, Communication and Technology (ICT) sector continues to grow in most of the global economies including South Africa. Growth within the sector is attributed to constantly emerging start-up and small micro medium enterprises, adding more competition and forcing incumbents to change the way they do business. Many companies struggle to adapt quickly to rapidly changing technologies that often disrupts existing markets and sometimes introduce new markets. Given TMT sector dynamics and challenges, small and large companies within the sector have recently started embracing mergers and acquisitions (M&A) as a growth and defence strategy to ensure that they remain relevant, retain existing markets, expand and venture into new markets in order to continue to create and sustain shareholders value. According to Institute of Management Accountants (1997), the linkage between strategy and value creation can be summarized by two simple laws of value creation; the first law is that management must create value for shareholders; and the second law is that all other stakeholders should also be satisfied in a way that contributes to shareholders value; and the company‟s ability to continue to attract capital by providing incremental value to shareholders is exactly what will allow it to continue to provide attractive products to its customers, attractive employment to its staff, and opportunities for its suppliers. M&A strategies should be executed with the same objective in mind to ensure shareholders value creation. This study investigated M&A performance within the TMT sector in South Africa to understand if they are creating shareholders value given the fact that some of the M&A transactions have failed in the past. The main objective of this research is to assess M&A performance and impact on shareholders value.